Financial technology: digital legal challenges and Indonesia's economic prospects after Covid-19 outbreak - Muslih, Muhammad; Supeno, Supeno (Faculty of Law, University of Muhammadiyah Malang, 2022)
Online loans are one of the financing business models organized using applications on the internet, the online loan business is currently developing so fast because it offers loans that can reach a sufficiently large amount with easy terms, procedures, and transaction processes, all intended to improve people's economic conditions. However, its implementation still sparks many legal problems and presents challenges for digital law in Indonesia. This study aims to study the challenges faced by Indonesian digital law due to the growth of the online loan business and to explore how the prospects of the online loan (fintech) business in improving the economic conditions of the Indonesian people. This research used empirical juridical methods, a case, and a statutory approach. The results showed that the challenges faced by Indonesian law in anticipating the growth of online businesses tainted by various legal cases require a more comprehensive rule of law in the form of legislation, thereby supporting the growth of prospects of the online loan business in an effort to improve the economy of the people of the state.